Are psychiatric disorders associated with thyroid hormone therapy in adolescents and young adults with type 1 diabetes?. Issue 7 (11th January 2021) - Eckert, Alexander; Galler, Angela; Papsch, Matthias; Hess, Melanie; Holder, Martin; Döing, Carsten; Bierkamp‐Christophersen, Dirk; Hammer, Elke; Pappa, Angeliki; Lanzinger, Stefanie
Abstract: Background: To evaluate the association between thyroid autoimmunity and psychiatric disorders (depression, anxiety, eating disorder, schizophrenia or attention‐deficit/hyperactivity disorder) among adolescents and young adults with type 1 diabetes (11‐25 years). Methods: We compared 9368 type 1 diabetes patients with thyroid autoimmunity (3789 of them treated with levothyroxine) with 62 438 type 1 diabetes patients without any thyroid disease from a multicentre diabetes patient follow‐up registry (DPV) in terms of psychiatric disorders. Thyroid autoimmunity was defined as documented diagnosis of Hashimoto thyroiditis or positive antibodies against thyroid peroxidase or thyroglobulin. Multivariable logistic regression models were used to calculate odds ratios for the respective psychiatric disorders in type 1 diabetes patients with thyroid autoimmunity (overall and stratified by levothyroxine therapy) compared to type 1 diabetes patients without thyroid diseases (reference). Results: Of the 9368 patients with thyroid autoimmunity, 62% were female with a median (Q1‐Q3) age of 16.3 (14.2‐17.6) years. Thyroid autoimmunity (with or without levothyroxine therapy) revealed a slight, but significant higher chance for depression (odds ratio [OR], 1.35, 95% confidence interval [CI], 1.19, 1.52), eating disorder (OR, 1.25, CI, 1.03, 1.51), attention‐deficit/hyperactivity disorder (OR, 1.22, CI, 1.07, 1.39) and schizophrenia (OR, 1.63, CI, 1.04, 2.56). In individuals with prescribed levothyroxine therapy because of thyroid dysfunction significantly higher odds for depression (OR, 1.63, CI, 1.34, 1.99), anxiety (OR, 1.60, CI, 1.18, 2.18), and attention‐deficit/hyperactivity disorder (OR, 1.71, CI, 1.38, 2.12) were observed compared to reference. Thyroid autoimmunity without required levothyroxine therapy revealed no differences to the reference group. Conclusions: Patients on levothyroxine had significantly higher odds for psychiatric disorders, but thyroid autoimmunity in terms of high antibody levels only did not show higher odds for any psychiatric disorder. Abstract : Highlights Several psychiatric disorders were associated with levothyroxine therapy (LT4). Depression, anxiety disorders, and attention‐deficit/hyperactivity disorder showed the strongest relation to LT4. Thyroid autoimmunity itself (no LT4) was not associated with psychiatric disorders. 摘要: 背景: 探讨青少年和青壮年(11 25岁)1型糖尿病患者甲状腺自身免疫功能与精神障碍(抑郁、焦虑、进食障碍、精神分裂症或注意力缺陷/多动障碍)的关系。 方法: 我们比较了9368例有甲状腺自身免疫性疾病的1型糖尿病患者(其中3789例接受左旋甲状腺素治疗)和62438例来自多中心糖尿病患者随访登记(DPV)的无甲状腺疾病的1型糖尿病患者的精神障碍。甲状腺自身免疫疾病被定义为有记录的桥本甲状腺炎或甲状腺过氧化物酶或甲状腺球蛋白抗体阳性。用多变量logistic回归模型计算有甲状腺自身免疫性疾病的1型糖尿病患者与无甲状腺疾病的1型糖尿病患者各自精神障碍的优势比(OR)。 结果: 9368例甲状腺自身免疫病患者中，62%为女性，中位年龄(Q1 Q3)为16.3(14.2 17.6)岁。甲状腺自身免疫性疾病(接受或不接受左旋甲状腺素治疗)显示抑郁(OR，1.35，95%置信区间[CI]，1.19，1.52)、进食障碍(OR，1.25，CI，1.03，1.51)、注意力缺陷/多动障碍(OR，1.22，CI，1.07，1.39)和精神分裂症(OR，1.63，CI，1.04，2.56)发生的几率略高，且存在显著性差异。与对照组相比，因甲状腺功能障碍而接受左甲状腺素治疗的个体患抑郁症(OR，1.63，CI，1.34，1.99)、焦虑(OR，1.60，CI，1.18，2.18)和注意力缺陷/多动障碍(OR，1.71，CI，1.38，2.12)的几率显著增加。不需要左旋甲状腺素治疗的甲状腺自身免疫性疾病与对照组没有差异。 结论: 服用左旋甲状腺素的患者患精神疾病的几率明显较高，但仅高抗体水平的甲状腺自身免疫疾病并不显示任何精神疾病的发病率增高。